2020
DOI: 10.1007/s40291-020-00446-x
|View full text |Cite
|
Sign up to set email alerts
|

Hemolysis and Fetal Fraction in Cell-Free DNA Blood Collection Tubes for Noninvasive Prenatal Testing

Abstract: Background Lysis of maternal white blood cells in prenatal cell-free DNA (cfDNA) test samples increases the level of maternal DNA and consequently decreases fetal fraction. Objective The objective of this study was to determine whether hemolysis, traditionally used as a marker for cell lysis, is correlated with a decrease in fetal fraction in maternal blood samples collected in specialized cfDNA tubes for noninvasive prenatal testing. Methods In the first part of the study, blood from pregnant women was collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…noticeably increase when improper operation occurs and/or there is a longer preservation time. Some researchers have shown that the increased FHb concentration can reflect the destruction of red blood cells, which is not synchronized with the release of DNA from white blood cell lysis [23,24]. In our study, samples collected in ImproGene tubes showed the results consistent with the conclusion mentioned above while Streck tubes had only a weak correlation; the cfDNA concentration in EDTA tubes markedly increased with FHb concentration (Figure 1).…”
Section: Discussionsupporting
confidence: 87%
“…noticeably increase when improper operation occurs and/or there is a longer preservation time. Some researchers have shown that the increased FHb concentration can reflect the destruction of red blood cells, which is not synchronized with the release of DNA from white blood cell lysis [23,24]. In our study, samples collected in ImproGene tubes showed the results consistent with the conclusion mentioned above while Streck tubes had only a weak correlation; the cfDNA concentration in EDTA tubes markedly increased with FHb concentration (Figure 1).…”
Section: Discussionsupporting
confidence: 87%
“…Second, other researchers have studied the effects of maternal and fetal characteristics and experimental factors on fetal fraction with the aim of adjusting these factors to obtain higher numbers of fetal-derived cfDNA. Fetal fraction can be influenced by maternal body mass index (BMI), gestational age (GA), anticoagulation therapy, blood collection, and fetal aneuploidy ( 14 , 18 , 19 ). Based on prior research, one potential way to reduce the incidence of screening failure is to repeat test failures by sequencing a second sample.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of hemolysis on NIPT has not been well investigated. A recent study showed that hemolysis in Cell-Free DNA Collection Tubes had no impact on the fetal fraction in NIPT [ 19 ]. One of the limitations of this study was that the hemoglobin concentration was assessed visually rather than with automated spectrophotometric instrumentation.…”
Section: Introductionmentioning
confidence: 99%